PEMBELAJARAN GERAK LURUS MELALUI MODEL PEMBELAJARAN GUIDED DISCOVERY DISERTAI LKS DI KELAS X MA NEGERI 1 JEMBER - Iqbal Bunga Pertiwi; Sudarti Sudarti; Pramudya Dwi Aristya Putra (FKIP Universitas Jember, 2017)
Guided discovery is a learning model that can expect students to identify knowledge and organize to final concept that is helped by LKS. This type of research is experimental research held in MA Negeri 1 Jember. The purpose of this study are to assess the influence of guided discovery learning for student’s cognitive learning outcomeon in straight motion learning,to assess the influence of guided discovery learning for student’s affective ability in straight motion learning, and to assess the influence of guided discovery learning to student’s science skill process in straight motion learning. Data collection technique use tests, observations, portofolios, interviews and documentation. Reseach testing by using analyse of Independent Sample t-test with SPSS IBM 23. The result show that guided discovery learning model significantly influence to student’s cognitive learning outcomeon in straight motion learning, that guided discovery learning model significantly influence student’s affective ability in straight motion learning, guided discovery learning model significantly influence to student’s science skill process in straight motion learning. Keyword: Guided Discovery, Cognitive Learning Outcomes, Affective Ability, Science Skill Process